SISTEM PENDUKUNG KEPUTUSAN UNTUK MENENTUKAN MAKANAN BAGI ANAK PENDERITA OBESITAS MENURUT GOLONGAN DARAH MENGGUNAKAN METODE LOGIKA FUZZY SUGENO PADA RUMAH SAKIT IBU DAN ANAK ANNISA JAMBI: Decision Support System, Diet Food, Obesity - Mulyati, Sri; Ulia, Efni (LP2M Universitas Nurdin Hamzah, 2017)
Obese people among children is increasing compared with previous years. This condition is very apprehensive because the childhood that they should be able to play and activities like peers but they must suffer due to excess weight. The method that will be applied in this system is using fuzzy sugeno logic method which will make easy for food determination process for obese child. Decision Support System is expected to help parents in controlling the condition of children who are suffering from obesity so that it can facilitate the process of restoring the condition of the child to be back to normal like children his age